Impact of Profitability, Liquidity, Solvency, Institutional Ownership, and Activity on Investment Decisions in IDX 80 Companies Listed on the Stock Exchange from 2016-2021 - Yohanes Theodorus; Jhon Lismart Benget P; Joseph Berlin Fernando Hutajulu; Belthasar Trito Siahaan (Journal of Research in Business, Economics, and Education, 2023)
The purpose of this study was to determine the effect of profitability, liquidity,solvency, institutional ownership, and activity on investment decisions. The population for this study was collected from 80 companies that were specifically selected according to certain criteria, to become 28 companies. The data used in this research is quantitative. Source of data in this research is secondary data. Data collection was done by writing method and data analysis was done by different linear test, F test and t test. (Y) can be explained by variations in profitability, liquidity, solvency, institutional ownership, and activity on investment decisions, while the remaining 63.5% is explained by other factors not included in this study. The results of the study partially show that institutional ownership and performance have a positive and significant effect on investment decisions, profitability has no significant negative effect on investment decisions, and liquidity and solvency have no significant effect on investment decisions. The research findings also show that profitability, liquidity, solvency, and institutional ownership influence investment decisions.